2006
DOI: 10.1002/art.21934
|View full text |Cite
|
Sign up to set email alerts
|

Nephritogenic Anti‐DNA antibodies regulate gene expression in MRL/lpr mouse glomerular mesangial cells

Abstract: Objective. Lupus-associated IgG anti-doublestranded DNA antibodies are thought to be pathogenic in the kidney due to cross-reaction with glomerular antigens, leading subsequently to immune complex formation in situ and complement activation. We undertook this study to determine if pathogenic anti-DNA antibodies may also contribute to renal damage by directly influencing mesangial gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
72
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 42 publications
9
72
0
Order By: Relevance
“…Moreover, urinary lipocalin-2 levels were increased in the mice up to 9 weeks after disease induction, coinciding with the presence of florid crescent formation. These results, together with our previous (9) and current data and the published evidence on an association between pediatric lupus nephritis and lipocalin-2 up-regulation (20), strongly support our assertion that urinary lipocalin-2 is a promising potential marker of renal involvement in SLE. As mentioned above, previous studies have indicated that other forms of renal injury, including ischemia, nephrotoxic drugs, or infection, can also up-regulate lipocalin-2 expression in the kidneys (14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, urinary lipocalin-2 levels were increased in the mice up to 9 weeks after disease induction, coinciding with the presence of florid crescent formation. These results, together with our previous (9) and current data and the published evidence on an association between pediatric lupus nephritis and lipocalin-2 up-regulation (20), strongly support our assertion that urinary lipocalin-2 is a promising potential marker of renal involvement in SLE. As mentioned above, previous studies have indicated that other forms of renal injury, including ischemia, nephrotoxic drugs, or infection, can also up-regulate lipocalin-2 expression in the kidneys (14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 90%
“…Pathogenic anti-dsDNA monoclonal antibodies up-regulate the expression of lipocalin-2 in glomerular mesangial cells in vitro and also in the kidneys when administered in vivo (9). In the present cross-sectional study, we showed that urinary lipocalin-2 was significantly higher in lupus patients with active nephritis than in those without nephritis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…[20][21][22][23][24] These antibodies were found to bind mainly nuclear antigens such as chromatin, histones and dsDNA, and/or components of the glomerular basement membrane. In particular, anti-dsDNA autoantibodies were found to be pathogenic and it has been shown that some anti-dsDNA autoantibodies can by themselves alter the gene expression profile of mesangial cell lines, turning on the expression of inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, anti-dsDNA autoantibodies were found to be pathogenic and it has been shown that some anti-dsDNA autoantibodies can by themselves alter the gene expression profile of mesangial cell lines, turning on the expression of inflammatory molecules. 24 Further studies are needed to evaluate whether the absence of antidsDNA autoantibodies in serum from IFNAR À/À (B6.Nba2 Â NZW)F1 mice is accountable for the lack of renal disease development in this model.…”
Section: Discussionmentioning
confidence: 99%